Estimating fat-free mass in elite youth male soccer players: cross-validation of different field methods and development of prediction equation - Munguia-Izquierdo, D.; Suárez-Arrones, L.; Di Salvo, V.; Paredes-Hernández, V.; Ara, I.; Mendez-Villanueva, A. (Journal of Sports Sciences, 2019)
This study determined the most effective field method for quantifying fat-free mass (FFM) in elite youth male soccer players compared to dual X-ray absorptiometry (DXA) values and to develop prediction equations for FFM based on anthropometric variables. Forty-one male elite-standard youth soccer players, ages 16.2-18.0 years, undertook FFM assessments including bioelectrical impedance analysis, and different skinfold-based prediction equations. DXA provided a criterion measure of FFM. Correlation coefficients, bias, limits of agreement, and differences were used as validity measures, and regression analyses to develop soccer-specific prediction equations. Slaughter et al (1988), Durnin and Wormersley (1974), and Sarria et al (1998) equations showed the lowest biases, and no significant, standardized, and substantial differences against DXA. The new youth soccer-specific anthropometric equation explained 91% of the DXA-derived FFM variance using three circumferences, eight skinfolds, and one bone breadth. All field methods compared in this study may not be adequate for estimating FFM in elite youth male soccer players, except the equations of Slaughter et al (1988), Durnin and Wormersley (1974), and Sarria et al (1998). We recommend the use of the new soccer-specific equation proposed in this study as a valid alternative to DXA to quantify FFM among elite youth male players.